EVALUATION OF POSSUM AND P - POSSUM SCORING SYSTEM IN ASSESING THE SURGICAL OUTCOME IN GENERAL SURGERY PATIENTS (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Accurate prediction of postoperative morbidity and mortality is essential in surgical practice for risk stratification and outcome assessment. The Physiological and Operative Severity Score for the Enumeration of Mortality and Morbidity (POSSUM) and its modification, Portsmouth-POSSUM (P-POSSUM), are widely used scoring systems designed to predict surgical outcomes. These tools help in clinical decision-making, auditing surgical performance, and improving patient care, especially in diverse general surgical populations. Aims: To evaluate and compare the accuracy of POSSUM and P-POSSUM scoring systems in predicting postoperative morbidity and mortality in general surgery patients. Materials and Methods: This prospective observational study was conducted over a period of 8 months in the Department of General Surgery at a tertiary care hospital. A total of 120 patients undergoing elective and emergency general surgical procedures were included. Preoperative physiological parameters and intraoperative operative variables were recorded for each patient to calculate POSSUM and P-POSSUM scores. Patients were followed postoperatively for complications and mortality. Observed morbidity and mortality rates were compared with predicted values, and the observed-to-expected (O) ratios were calculated. Statistical analysis was performed to assess the predictive accuracy of both scoring systems. Results: Out of 120 patients, postoperative morbidity was observed in 42 (35.0%) patients, while mortality occurred in 8 (6.7%) patients. POSSUM predicted higher morbidity (50.0%) and mortality (15.0%) compared to observed outcomes, indicating overestimation. In contrast, P-POSSUM showed better correlation, predicting morbidity at 38.0% and mortality at 8.5%. The observed-to-expected (O:E) ratio for morbidity was 0.84 for POSSUM and 0.92 for P-POSSUM, while for mortality it was 0.44 and 0.79 respectively. Higher scores were significantly associated with increased postoperative complications and mortality (p < 0.05). Patients undergoing emergency surgeries and those aged >50 years demonstrated higher morbidity and mortality rates. Overall, P-POSSUM showed superior predictive accuracy compared to POSSUM. Conclusion: Both POSSUM and P-POSSUM are valuable tools for predicting surgical outcomes; however, P-POSSUM provides a more accurate estimation of mortality and morbidity. These scoring systems can be effectively used for risk stratification, audit, and improving quality of care in general surgery patients.